Surgical Treatment for a Super-Giant Right Coronary Artery Aneurysm Induced by Kawasaki Disease - Kuroda,Yoshinori (2021)
Abstract A 32-year-old man diagnosed with Kawasaki disease at the age of three years presented with coronary artery aneurysm (CAA). The aneurysm increased in size, and the patient was referred to our hospital for surgery. Preoperative computed tomography scan showed a super-giant right CAA and giant left CAAs; surgery was performed. The super-giant right CAA was resected, and the ostium of the right coronary artery was closed; then, coronary artery bypass grafting was performed. The left CAAs were not treated surgically because the risk of rupture was low. Here, we describe the successful surgical treatment of a right super-giant CAA.